Frequency and Pattern of Retinopathy in Newly Diagnosed Type 2 Diabetic Patients: Retinopathy in Type 2 Diabetic Patients - Mehmood, Faisal; Mazhar, Syed Abdullah; Farooq, Nesr; Afzal, Muhammad Awais (Pakistan Journal of Health Sciences, 2025)
Diabetic Retinopathy (DR) is among the leading causes of blindness in adults, particularly in individuals with type 2 Diabetes Mellitus (T2DM). Diabetic Retinopathy (DR) is one of the commonest reasons for blindness in the adult population especially in the type 2 Diabetes Mellitus (T2DM) population. It is important to detect and manage these diseases early to prevent vision loss. Objective: To evaluate the prevalence and pattern and the associated risk factors of Diabetic Retinopathy (DR) in newly diagnosed T2DM. Methods: The study design was descriptive cross-sectional which was conducted at Arif Memorial Teaching Hospital/Rashid Latif Medical College, Lahore. The study enrolled 300 participants (age≥35 years) with newly diagnosed T2DM. After a general and systemic examination, data were collected, including laboratory data with blood glucose, HbA1c, serum cholesterol, and serum creatinine. Retinopathy grading was performed by fundoscopic examination into background, pre-proliferative and proliferative grades. The statistical analysis was performed in SPSS version 23.0. Results: In newly diagnosed T2DM, the overall prevalence of DR was 22% (66/300). Among cases of DR, 78% were NPDR, and 22% were PDR. Most of the NPDR was moderate (43%), mild (35%) and severe (22%). DR risk factors were HbA1c > 8% (OR: 3.5, p < 0.001) and hypertension (65% DR, p < 0.05). DR was not significantly correlated with BMI and other biochemical markers including serum creatinine. Conclusions: The prevalence of diabetic retinopathy was notably high among newly diagnosed T2DM patients, with HbA1c levels and hypertension identified as significant risk factors.